2012
DOI: 10.1371/journal.pgen.1002452
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for an Indispensable Role of Somatic Embryogenesis Receptor Kinases in Brassinosteroid Signaling

Abstract: The Arabidopsis thaliana Somatic Embryogenesis Receptor Kinases (SERKs) consist of five members, SERK1 to SERK5, of the leucine-rich repeat receptor-like kinase subfamily II (LRR-RLK II). SERK3 was named BRI1-Associated Receptor Kinase 1 (BAK1) due to its direct interaction with the brassinosteroid (BR) receptor BRI1 in vivo, while SERK4 has also been designated as BAK1-Like 1 (BKK1) for its functionally redundant role with BAK1. Here we provide genetic and biochemical evidence to demonstrate that SERKs are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
270
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(288 citation statements)
references
References 52 publications
13
270
2
3
Order By: Relevance
“…The notion that BAK1 and its paralogs may be the co-receptors of RGIs is supported by a few observations. First, serk1 bak1 bkk1 or serk1 serk2 bak1 triple mutants show short root phenotype which is independent of the BR signaling pathway [33,34]. Second, members of RGIs were found to interact with BAK1 in a yeast two-hybrid analysis (data not shown), which was the primary motivation prompted us to study the functions of the entire clade of RGIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that BAK1 and its paralogs may be the co-receptors of RGIs is supported by a few observations. First, serk1 bak1 bkk1 or serk1 serk2 bak1 triple mutants show short root phenotype which is independent of the BR signaling pathway [33,34]. Second, members of RGIs were found to interact with BAK1 in a yeast two-hybrid analysis (data not shown), which was the primary motivation prompted us to study the functions of the entire clade of RGIs.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory is interested in revealing the biological functions of these undefined LRR-RLKs. Our previous genetic analyses indicated that BAK1 and its paralogs are involved in regulating brassinosteroid (BR)-independent root growth and development, as serk1 serk2 bak1 and serk1 bak1 bkk1 triple null mutants show intensively shorter roots compared with BR-deficient or BR signaling-impaired mutants [33,34]. We proposed that BAK1 and its paralogs may serve as a co-receptor and pair with another LRR-RLK to regulate root growth and development, similar to its role in BRI1-or FLS2-mediated signaling pathway [35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of members of the SERK family that act redundantly in different signaling pathways Li, 2010;Du et al, 2012;Gou et al, 2012;Kim et al, 2013) has underscored the importance Figure 5. Prediction of BRI1 signaling output in the absence of SERK coreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory mechanism involves the BRI1 KINASE INHIBITOR1 (BKI1), which binds to the kinase domain of unliganded BRI1 receptors and thereby keeps the LRR-RLK inactive (Jaillais et al, 2011b). In vitro, BKI1 precludes BRI1 from associating with BRI1-ASSOCIATED KINASE1 (BAK1; also known as SOMATIC EMBRYO-GENESIS RECEPTOR-LIKE KINASE3 [SERK3]; Wang and Chory, 2006;Jaillais et al, 2011b), another LRR-RLK required for BR signal transduction Nam and Li, 2002;Gou et al, 2012). Binding of BRs to the extracellular LRR domain of BRI1 homodimers is thought to result in conformational changes, which trigger basal BRI1 kinase activity and autophosphorylation Kim and Wang, 2010;Jaillais et al, 2011a).…”
mentioning
confidence: 99%
“…The first is the observation by Gou et al (2012) that BAK1(SERK3), SERK1, and SERK4 (also known as BAK1-LIKE KINASE1) not only enhance BRI1 kinase activity but are essential for initiating downstream signal transduction. The second derives from the resolved crystal structure of the BRI1 ectodomain and opposes the hypothesis that BRI1 homodimers function as ligandperceiving receptor complexes.…”
mentioning
confidence: 99%